2020
DOI: 10.3390/genes11091097
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression with an Emphasis on Floral Organ Size Differences in Natural and Synthetic Polyploids of Nicotiana tabacum (Solanaceae)

Abstract: Floral organ size, especially the size of the corolla, plays an important role in plant reproduction by facilitating pollination efficiency. Previous studies have outlined a hypothesized organ size pathway. However, the expression and function of many of the genes in the pathway have only been investigated in model diploid species; therefore, it is unknown how these genes interact in polyploid species. Although correlations between ploidy and cell size have been shown in many systems, it is unclear whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 154 publications
0
9
0
Order By: Relevance
“…Accordingly, evolutionary biologists have had a great deal of interest in exploring the consequences of and responses to WGD. The ensuing studies have shown that the effects of WGDs are far-ranging, including the silencing and loss of duplicated genes ( Anssour et al 2009 ; Schnable et al 2011 ; Buggs et al 2012 ; Liu et al 2014 ; Mirzaghaderi and Mason 2017 ; Cheng et al 2018 ; Wendel et al 2018 ), mobilization of previously dormant transposable elements ( Petit et al 2010 ; Gao et al 2016 ; Senerchia et al 2016 ; Springer et al 2016 ; Vicient and Casacuberta 2017 ; Nieto Feliner et al 2020 ), intergenomic gene conversion and homoeologous chromosome exchanges ( Chester et al 2012 ; Chalhoub et al 2014 ; Guo et al 2014 ; Jarvis et al 2017 ; Chen et al 2018 ; Bertioli et al 2019 ; Li et al 2019b ; Mason and Wendel 2020 ), alterations of epigenetic marks ( Madlung et al 2002 ; Salmon et al 2005 ; Shcherban et al 2008 ; Fulneček et al 2009 ; Akagi et al 2016 ; Chen et al 2017a ; Song et al 2017 ; Ding and Chen 2018 ), massive, genome-wide transcriptional rewiring ( Schnable et al 2011 ; Combes et al 2013 ; Akama et al 2014 ; Hu et al 2016 ; Yang et al 2016 ; Edger et al 2017 ; Ramírez-González et al 2018 ; Oberprieler et al 2019 ; Landis et al 2020 ), and a host of other associated physiological, ecological, and life-history changes ( Stebbins 1940 ; Levin 1983 ; Otto and Whitton 2000 ; Ramsey and Schemske 2003 ; Otto 2007 ; Leitch and Leitch 2008 ; Van de Peer et al 2009 ; Ma...…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, evolutionary biologists have had a great deal of interest in exploring the consequences of and responses to WGD. The ensuing studies have shown that the effects of WGDs are far-ranging, including the silencing and loss of duplicated genes ( Anssour et al 2009 ; Schnable et al 2011 ; Buggs et al 2012 ; Liu et al 2014 ; Mirzaghaderi and Mason 2017 ; Cheng et al 2018 ; Wendel et al 2018 ), mobilization of previously dormant transposable elements ( Petit et al 2010 ; Gao et al 2016 ; Senerchia et al 2016 ; Springer et al 2016 ; Vicient and Casacuberta 2017 ; Nieto Feliner et al 2020 ), intergenomic gene conversion and homoeologous chromosome exchanges ( Chester et al 2012 ; Chalhoub et al 2014 ; Guo et al 2014 ; Jarvis et al 2017 ; Chen et al 2018 ; Bertioli et al 2019 ; Li et al 2019b ; Mason and Wendel 2020 ), alterations of epigenetic marks ( Madlung et al 2002 ; Salmon et al 2005 ; Shcherban et al 2008 ; Fulneček et al 2009 ; Akagi et al 2016 ; Chen et al 2017a ; Song et al 2017 ; Ding and Chen 2018 ), massive, genome-wide transcriptional rewiring ( Schnable et al 2011 ; Combes et al 2013 ; Akama et al 2014 ; Hu et al 2016 ; Yang et al 2016 ; Edger et al 2017 ; Ramírez-González et al 2018 ; Oberprieler et al 2019 ; Landis et al 2020 ), and a host of other associated physiological, ecological, and life-history changes ( Stebbins 1940 ; Levin 1983 ; Otto and Whitton 2000 ; Ramsey and Schemske 2003 ; Otto 2007 ; Leitch and Leitch 2008 ; Van de Peer et al 2009 ; Ma...…”
Section: Introductionmentioning
confidence: 99%
“…However, polyploidization might induce several important changes at the genetic, gene expression, and epigenetic levels 5 10 . In recent decades, many efforts have been made to produce synthetic allopolyploid species, such as Arabidopsis 11 , 12 , Brassica 13 , 14 , Oryza 15 , Nicotiana 16 , Triticum 17 and Gossypium 18 . Among them, Brassica species are one of the model systems to study crop allopolyploidization 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A de novo transcriptome assembly was generated to serve as a reference to identify candidate genes of interest for downstream analyses using Trinity v2.11.0 ( Grabherr et al, 2011 ; Haas et al, 2013 ) using both the cleaned Illumina short reads and Nanopore long reads by implementing the long-reads flag. This approach has been used previously in several studies to generate full length or nearly full length gene contigs in the reference transcriptome assembly to map Illumina short reads to for differential gene expression analysis ( Landis et al, 2020 ; Zhang et al, 2022 ). Contigs smaller than 250 bp in length were removed with seqkit v0.12.0 ( Shen et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%